Desarrollo de la plataforma de visita virtual a la Universidad Técnica de Cotopaxi Extensión La Maná con técnicas de geolocalización que faciliten la identificación de espacios y aproximación de búsqueda de personas por conjuntos. - Marmolejo Guerrero, Eliana Lizbeth (2022)
At present, technology is advancing that is why the Technical University of Cotopaxi, La Maná extension, sees the need to have a web application that allows the user to virtually see the infrastructure and green areas of the institution without the need to go to facilities, the virtual tour is aimed at students, teachers, administrative staff and all those who need to have information since the application is deployed in the cloud. In addition, students will be able to locate a teacher without major inconveniences thanks to the information available on the platform in question, which is classified according to the University hours. The main objective of the virtual visit platform to the Technical University of Cotopaxi, La Maná extension, with geolocation techniques that facilitate the identification of spaces and the search for people by groups, is to disseminate the physical infrastructure and technology in 360-degree panoramic images providing information on the services offered by the University to the Lamanense community.